Penerapan Metode Promethee Pada Sistem Pendukung Keputusan untuk Kenaikan Jabatan Struktural Pemerintahan - Jemsrado Sine (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
Decision support system (DSS) for structural promotion to Echelon IV in Board of Regional Civil Service (BRCS) of Kupang City is made under Regulation of Employee Legislation that regulates the election provisions and terms of Echelon IV officials. DSS is created with the aim of helping the BRCS of Kupang City in the selection process of Echelon IV structural officials in order to be more objective and effective in administration by using the PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation) method, the way is to determine and set criteria and criterion parameters appropriately and in accordance with the functions of PROMETHEE preference criteria. All the criteria and parameters refer to the selection rules of Echelon IV structural officials. We can conclude from the results of this study that the PROMETHEE DSS method as a multi-criteria method can help the BRCS of Kupang City in the selection process of Echelon IV structural officials more objective and effective in administration since it is analyzed / processed electronically based on the database of employee management information systems and refer to the employment laws. Determination of criteria, criterion parameters and criterion priority dominance is very influential on the decision-making process because it helps to determine the level of competence, performance and high responsibility for the employees in the structural position of Echelon IV.